How the Federalism Structure in America Impacted the Planning Stage for a Pandemic: COVID 19 as a Case Study - Abuelghanam, Debbie (Dirasat: Human and Social Sciences, 2023)
Objective: The objective is to examine how the tension between the federal, state, and local levels affects the planning, lockdown, and reopening of the economy during the pandemic. To date, COVID-19 kills one American every 30 seconds. As this tragedy continues to claim thousands of lives, many Americans point to the US government's failure to respond to the pandemic effectively and efficiently. Method: Method: The article uses the descriptive method to explain how the American federalism structure affected pandemic planning. It utilizes COVID-19 as a case study. Results: The study found increased tensions between the President and state Governors, among federal departments, and between federal and state agencies, which were exacerbated by the pandemic. The governors counterbalanced the lack of presidential leadership. However, the President interfered with federal agencies and governors, attempted to influence agency budgets and threatened governors for their lack of appreciation and loyalty. Regional coalitions, while having little influence during the planning stages, affected the procurement of medical supplies and equipment, state leadership and reopening state economies. Conclusion: Overall, the federalist structure c